Analisis Penerapan Praktik Green Supply Chain Management di PT. Basundari Inovasi Muda - Mulyani, Enci; Lestari, Sofiana Tri; Rahmah, Hasna Nur; Safa'at, Muhammad Alim (Jurnal TRINISTIK: Jurnal Teknik Industri, Bisnis Digital, dan Teknik Logistik, 2024)
A comprehensive analysis of the implementation of Green Supply Chain Management at PT Basundari Innovation Muda highlights a strategic approach to sustainable practices in the supply chain. The goal is to reduce impacts and increase resource efficiency. The research evaluative method identifies gaps between current practices and the ideal GSCM system through observations, interviews, and literature studies, focusing on three supply chain components: upstream, internal, and downstream. Even though the company has implemented several GSCM practices, there are still gaps, especially in using non-environmentally friendly materials and consistency in implementing practices throughout the supply chain. Recommendations include selecting environmentally friendly suppliers and improving managerial training regarding GSCM.